1987
DOI: 10.1002/ajh.2830250102
|View full text |Cite
|
Sign up to set email alerts
|

Immunological aspects of the anemia of rheumatoid arthritis

Abstract: In order to investigate the cause of the anemia concomitant with rheumatoid arthritis (RA), we examined, using the erythroid colony assay of human bone marrow colony-forming units-erythroid (CFU-e) and burst-forming units-erythroid (BFU-e), the effects of the patients' serum and peripheral blood T lymphocytes on the CFU-e-derived colonies. The counts of erythroid colonies of RA patients were markedly lower than those of human control subjects [CFU-e: control 152.9 +/- 30.6 (n = 19), RA 51.1 +/- 13.6 (n = 7), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…To establish this one could add serum from anemic RA patients with and without anti-TNFcr to bone marrow cultures. However, in our experience which is shared by others [42] the results of serum addition to marrow cultures are variable and inconsistent probably due to the presence of other undefined endotoxines and lipopolysaccharides, whereas, as discussed previously, serum TNFcr concentrations may be lower than necessary for in uitro suppression.…”
Section: Values Indicate Numbers Of Bfue Per Lo5 Cells (Median; Rangementioning
confidence: 44%
“…To establish this one could add serum from anemic RA patients with and without anti-TNFcr to bone marrow cultures. However, in our experience which is shared by others [42] the results of serum addition to marrow cultures are variable and inconsistent probably due to the presence of other undefined endotoxines and lipopolysaccharides, whereas, as discussed previously, serum TNFcr concentrations may be lower than necessary for in uitro suppression.…”
Section: Values Indicate Numbers Of Bfue Per Lo5 Cells (Median; Rangementioning
confidence: 44%
“…Other studies have also implicated T-lymphocytes as inhibitors of erythropoiesis in chronic inflammatory disorders. Sugimoto et al (1989) reported that T-lymphocytes from anemic patients with rheumatoid arthritis inhibited the growth in vitro of normal CFU-E relative to T-lymphocytes from normal subjects.…”
Section: Discuss I 0 Nmentioning
confidence: 91%
“…Sugimoto et al (1989) reported that T-lymphocytes from anemic patients with rheumatoid arthritis inhibited the growth in vitro of normal CFU-E relative to T-lymphocytes from normal subjects.…”
Section: Discuss I 0 Nmentioning
confidence: 98%
“…Cells derived from the bone marrow of RA patients showed less effective colony formation potency when compared to HC-derived bone marrow cells [191-193]. Further studies confirmed the reduced proliferative capacity of CD34+ HSC from RA patients [194-198].…”
Section: The Nine Hallmarks Of Aging and Ramentioning
confidence: 99%